Neurodevelopmental impact of early diagnostic imaging in preterm infants: quantifying risk and the role of point-of-care ultrasound - Bhattacharjee, Indrani; Volpe, MaryAnn; Bhattacharya, Siddharth; Sibley, Cecelia; Church, Paige (Frontiers in Pediatrics, 2025)
BackgroundMedical imaging is essential in neonatal intensive care units (NICUs), particularly for the management of preterm infants. However, concerns persist regarding the neurodevelopmental impact of repeated low-dose radiation exposure. This study aimed to investigate whether cumulative x-ray exposure in the first month of life is associated with neurodevelopmental outcomes in preterm infants.MethodsWe conducted a retrospective chart review of preterm infants (<34 weeks gestation) admitted to the Level IIIB NICU at Tufts Medical Center. Infants were included if they had at least one x-ray within the first 24 h of life and were followed consistently at the neurodevelopmental clinic till 12–18 months corrected age. Exclusion criteria included major congenital anomalies, severe perinatal complications and loss to follow-up. Cumulative x-ray exposure was recorded at Day 1, Day 7, and Month 1. Neurodevelopment was assessed using Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III). Multiple linear regression analyses were used to assess associations, adjusting for gestational age, birth weight, comorbidities and SNAPPE-II scores.ResultsAmong 53 infants, cumulative imaging by Day 7 and Month 1 was significantly associated with lower Bayley-III motor and cognitive scores. Each additional x-ray by Day 7 was associated with a 1.38-point decline in motor scores (p < 0.001) and a 0.89-point decline in cognitive scores (p = 0.046). These associations persisted at Month 1. No significant effects were found for imaging on Day 1. Language outcomes showed non-significant downward trends.ConclusionFrequent x-ray exposure in the first month of life may be associated with worse motor and cognitive development in preterm infants. These findings suggest the need for weight-based diagnostic reference levels in NICUs and support incorporation of alternative imaging such as point of care ultrasound (POCUS into routine neonatal intensive care.